Masterpieces of Swiss Entrepreneurship Swiss SMEs Competing in Global Markets - Jeannet, Jean-Pierre (Springer Nature, 2021)
This open access book focuses on Switzerland-based medium-sized companies with a longstanding export tradition and a proven dominance in global niche markets. Based upon in-depth documentation and analysis of 36 Swiss companies over their entire history, an expert team of authors presents several parallels in the pathways and success factors which allowed these firms to become dominant and operate from a high-cost location such as Switzerland. The book enhances these insights by providing detailed company profiles documenting the company history, development, and how their relevant global niche positions were reached. Readers will benefit from these profiles as they compile a diverse selection of industries, mainly active within the B2B sector, with mostly mature companies (60 years to older than 100 years since founding) and different types of ownership structures including family firms. 'Masterpieces of Swiss Entrepreneurship' brings unique learning opportunities to owners and leaders of SMEs in Switzerland and elsewhere. Findings are based on detailed bottom-up research of 36 companies -- without any preconceived notions. The book is both conceptual and practical. It fosters understanding for different choices in development pathways and management practices. Matti Alahuhta, Chairman DevCo Partners, ex-CEO Kone, Board member of several global listed companies, Helsinki, Finland Start-up entrepreneurs need proven models from industry which demonstrate the various paths to success. "Masterpieces of Swiss Entrepreneurship" provides deep insights highlighting these models and the important trade-offs entrepreneurial teams must consider when choosing the path of high growth or of maximum control, as they are often mutually exclusive. Gina Domanig, Managing Partner, Emerald Technology Ventures, Zurich ;